Crystal structure of a family 6 cellobiohydrolase from the basidiomycete Phanerochaete chrysosporium. Issue 7 (1st July 2017) - Tachioka, Mikako; Nakamura, Akihiko; Ishida, Takuya; Igarashi, Kiyohiko; Samejima, Masahiro
Abstract : The crystal structure of the catalytic domain of a glycoside hydrolase family 6 cellobiohydrolase from the basidiomycete P. chrysosporium was solved in apo and cellobiose‐liganded forms at 1.2 and 2.1 Å resolution, respectively. Abstract : Cellobiohydrolases belonging to glycoside hydrolase family 6 (CBH II, Cel6A) play key roles in the hydrolysis of crystalline cellulose. CBH II from the white‐rot fungus Phanerochaete chrysosporium ( Pc Cel6A) consists of a catalytic domain (CD) and a carbohydrate‐binding module connected by a linker peptide, like other known fungal cellobiohydrolases. In the present study, the CD of Pc Cel6A was crystallized without ligands, and p ‐nitrophenyl β‐d ‐cellotrioside ( p NPG3) was soaked into the crystals. The determined structures of the ligand‐free and p NPG3‐soaked crystals revealed that binding of cellobiose at substrate subsites +1 and +2 induces a conformational change of the N‐terminal and C‐terminal loops, switching the tunnel‐shaped active site from the open to the closed form.